(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article examines the effective strategies and tools that support language learning for blind and visually impaired individuals. It explores adaptive teaching methods, emphasizing the importance of auditory-based instruction, tactile resources such as braille, and the use of assistive technologies like screen readers and speech synthesis. The article highlights the role of personalized learning plans tailored to individual needs, along with the significance of fostering an inclusive environment. Tools such as audiobooks, interactive auditory learning platforms, and collaborative peer learning are discussed as ways to enhance language comprehension and fluency. The importance of teacher training in inclusive education is also stressed, ensuring that educators can implement these tools effectively. Ultimately, the article advocates for a more adaptive and inclusive approach to language education that empowers visually impaired learners to succeed.